Social Entrepreneurship Attitudes and Activity in Indonesia - Fiona Ekaristi Putri; Gandhi Pawitan; Maria Widyarini (UPPM Politeknik TEDC Bandung, 2019)
Indonesia is on the second place in terms of entrepreneurial intention and has 17.67% of early-stage entrepreneurial activity, which is the highest number in 2015 among five ASEAN countries. This phenomenon shows that Indonesia has the potential to develop more established entrepreneurs, including social entrepreneurs. The social entrepreneurs are aiming to change the society into a better one. The social entrepreneurs receive higher status in the society when their businesses could affect and change the society positively and exceedingly when their businesses are exposed by the media. Global Entrepreneurship Monitor study at national level shows that social entrepreneurs in Indonesia are more likely to engage with one another to solve the issues in the society. Moreover, findings show that perceived capabilities from social entrepreneurs are lower than traditional entrepreneurs. It might happen because social entrepreneurs need to exercise social innovation higher than other entrepreneurs. Thus they were expected to have higher capabilities.